Impact of Child Marriage in Terms of Household Harmony: Study in Dander District, Bojonegoro Regency - Mulyani, Sri; Aljaberi, Musheer Abdulwahid; Ahmed, Idris Adewale (PT. Riset Press International, 2025)
Child marriage is a phenomenon that affects the quality of household life, especially among young people who are still studying. Psychological immaturity is often the leading cause of conflict and disharmony in the household. This study aims to identify household harmony in child marriage in Dander District, Bojonegoro Regency. This study uses a descriptive design with a survey approach. The population consists of 27 families who had child marriages in 2022, with a sampling technique using saturated sampling. Data was collected through questionnaires and analyzed through editing, coding, scoring, and tabulation processes to determine the percentage. The results showed that more than half of the respondents (51.9%) had a level of household harmony classified as disharmonious. The main factors contributing to this disharmony are a lack of communication, unmanaged conflicts, and a lack of joint planning between couples. The conclusion of this study is that child marriage tends to result in household disharmony. Therefore, efforts are needed to improve communication between couples, healthy conflict management, and discussions to plan common goals both in the short and long term. These results are expected to be evaluation materials for the government and society to prevent child marriage through more effective education and regulation.